Criminal Law Policy in Tackling Personal Possession of Marijuana for Medicine - Alviolita, Fifink Praiseda; Arzaqi, Nila (Bacarita Law Journal, 2025)
The problem of personal possession of marijuana for medical purposes because according to the mandate of the constitution the right to life is guaranteed by the 1945 Constitution. The purpose of this study is to identify problems from the formulation aspect of the Narcotics Law to determine the appropriate criminal law policy to overcome these legal issues. This study uses a type of normative juridical research with a qualitative approach. The results of the study show that the Narcotics Law has a vagueness of norms that results in a person who has marijuana personally for treatment or therapy can be criminalized, even though if you look at the formulation of the Narcotics Law does not really prohibit it as long as it is in accordance with the results of research so that its use can be scientifically proven. In addition to the incessant eradication of narcotics trafficking and abuse, the government needs to take policies by revising the Narcotics Law. Efforts that can be made by decriminalizing personal possession of marijuana as a treatment does not mean that it will be impossible in the future, coupled with the regulation and supervision of marijuana trafficking, will open up space for the courts to focus on dealing with more serious narcotics crimes. This means that the government must be present to refocus the function of legislation and determine future regulations to regulate the maximum limit on the amount of psychotropic substances that can be legally owned or not so that they can distinguish the perpetrators of criminal acts whether they are categorized as owners, users, storers or dealers and the certainty of psychotropic abuse in order to achieve certainty, justice and usefulness.